Study Eksperimental : Distraksi Rompi Bermotif Kartun Terhadap Perilaku Kecemasan Anak Di Denpasar - Sukmandari; Wulandari; Dewi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
The process of hospitalization in children tends to cause negative behaviors, so the purpose of this study wantsto know the effect of cartoon motif vest distraction techniques on the anxiety behavior of preschool-agechildren. The design uses Experimental Quasi which is Pre-Test and Post-Test with Control Group Design,sample number 50, and consecutive sampling technique. Data analysis using the Wilcoxon sign rank test andMann Whitney with significance 0.05. The results showed there was an influence of cartoon motif vestdistraction techniques on the intervention group and the use of motifless vests in the control group with pvalues of 0.000 and 0.013 respectively and no difference between the abstraction technique of the use ofcartoon motif vests and motifless vests with a p-value of 0.359. It is expected that nurses in the childcare roomwill wear uniforms with the motives or colors that children like.